Bread grabbed from a half closed door. Nomad subjects in ethnography. - Spagna, Francesco (Anthropology & Humanism, 2025)
The title expression came to the fore while conducting a research on the representations of hospitality of individuals and families from East Africa in the city of Padua, Italy. The research focused on traditional representations of "unconditional hospitality" prevalent in Somalia, Ethiopia, and Eritrea (former Italian colonies) and how these representations, conceptions, and values were maintained or negotiated in the host society. A woman from Mogadishu tells of arriving in Padua and staying in an apartment building. In her representation of hospitality, arriving in a multi‐family dwelling such as a condominium creates a situation that would imply an offering to the community where she arrived as a guest. She knew that Italians like Arabic bread. Therefore, she prepared some loaves of bread and rang her neighbors to donate them. The neighbors opened the door, but when ajar, they stuck their hand out to take the bread and immediately closed it again. The amusing episode allows one to trigger, in the ethnographic interview, a shared reflection and a complicity. It opens up to a wider dimension, calling up the themes of welcoming, integration, hospitality, fear of the other, ambivalence, the meanings of food and conviviality, the "condominium situation," a set of aspects that involve the ethnographer himself, in his own incomplete integration in the city where he lives.